Development of Multimedia-Based Mobile Learning in Class X SMKN Informatics Subjects - Hariadi, Syarif Novalin; Hendri, Nofri; Hidayati, Abna; Zuliarni, Zuliarni (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research discusses the development of multimedia-based mobile learning in class X informatics subjects of SMKN. The purpose of the research is to develop a mobile learning product based on multimedia in class X informatics subjects at SMKN. This research method is development research (R&D) with a 4D development model. The population in this study was all grade X students at SMKN 1 West Pasaman. The sample of this study amounted to 25 respondents taken from one class X at SMKN. The data collection tool used a questionnaire with a total of 19 question items. The data analysis technique used is descriptive quacitivative, using Likert scale. The results of research on learning media development by media validators 1 and 2 were obtained " 4.95" with the category "Very Valid". For material validators on the feasibility aspects of content, presentation, and evaluation, "4.10" was obtained with the category "Valid". The results of the practicality test to students on multimedia, it was concluded that the assessment carried out by students obtained results of “4.53” with the category "Very Practical"